Bioenergy feedstocks : breeding and genetics - Saha, Malay; Bhandari, Hem Singh; Bouton, Joseph H. (Joseph Henry), 1948- ([Hoboken, N.J.] : Wiley-Blackwell, 2013)
This book looks at advances in our understanding of the genetics and breeding practices across this diverse range of crops and provides readers with a valuable tool to improve cultivars and increase energy crop yields.
Switchgrass genetics and breeding challenges -- Switchgrass genomics -- Germplasm resources of Miscanthus and their application in breeding -- Breeding Miscanthus for bioenergy -- Breeding sorghum as a bioenergy crop -- Energy cane -- Breeding maize for lignocellulosic biofuel production -- Underutilized grasses -- Alfalfa as a biofuel crop -- Transgenics for biomass -- Endophytes in low input agriculture and plant biomass production.
Includes bibliographical references and index.
Print version record.
Keywords: Energy crops; Energy crops -- Breeding; Energy crops -- Genetics; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Electronic books